Cytological findings of odontogenic myxofibroma: A diagnostic dilemma. Issue 4 (23rd January 2016) - Khare, Akriti; Joshi, Deepti; Majumdar, Kaushik; Gupta, Vikas; Goel, Garima; Kapoor, Neelkamal
Abstract : Odontogenic myxofibroma represents a rare slow‐growing benign neoplasm, which usually occurs in the second and third decades of life and rarely in children or adults over 50 years of age. Myxomas in general represent from 2.3% to 17.7% of all odontogenic tumors, and myxofibromas represent a small number of all myxomas. Limited evidence is present in literature regarding the cytological diagnosis of odontogenic myxoma/myxofibroma. We hereby report the cytomorphological features of a histologically confirmed case of odontogenic myxofibroma and the pitfalls of the cytological diagnosis. A painless jaw swelling in a young boy was aspirated. Scanty mucoid material was obtained. Cytology Smears were moderately cellular and showed a population comprising predominantly of singly scattered plump to fusiform cells with bipolar cytoplasmic processes showing mild to moderate atypia embedded within dense myxoid matrix and another population of cells arranged in clusters. Case was interpreted as low grade mesenchymal tumor. Subsequent biopsy confirmed it as odontogenic myxofibroma arising in a odontogenic keratocyst. Precise interpretation of intraosseous jaw lesions FNAC may not always be possible, but an attempt should be made to broadly classify the lesion as an inflammatory lesion, cystic lesion, giant cell lesion, fibro‐osseous lesion or as an odontogenic tumor. If dual population of odontogenic epithelium and mesenchymal cells embedded in myxoid matrix are identified in such aspirates, a possibility of myxoid odontogenic tumor may be suggested. Triple correlation of cytological, clinical and radiological findings can guide the surgeon for taking appropriate therapeutic decisions. Diagn. Cytopathol. 2016;44:329–333. © 2016 Wiley Periodicals, Inc.